Perbedaan Resiko Gangguan Psikososial pada Remaja Positive Smartphone Addiction dan Negative Addiction di SMA Kota Sungai Penuh Tahun 2019 - Edi Efian; Rizanda Machmud; Mahathir Mahathir; Meri Neherta; Rima Berlian Putri; Fitra Yeni (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Excessive use of smartphones poses a risk of addiction, smartphone addiction will affect psychological health which has an effect on psychosocial disorders. Teenagers are a vulnerable period that easily accepts new cultures, smartphone technology culture is one that lurks teenagers. Objective: This study is to determine the differences in the risk of psychosocial disorders in adolescents with positive smartphone addiction with negative smartphone addiction. This research is a quantitative study with cross sectional design, data collection using the smartphone addiction scale (Short-version) questionnaire and pediatric symptom checklist (PSC-17), the population of adolescents in high schools in Sungai Penuh city, a sample of 350 people , the conscientious variable consists of the independent variable smartphone addiction and the dependent variable psychosocial disorders in adolescents. There was a difference in the risk of psychosocial disorders in adolescents, 60/25 men experienced psychosocial disorders (p = 0,000) OR 3,936. In adolescent girls 50/47 experience psychosocial disorders (0.004) OR 2,437. Teen positive smartphone addiction is at greater risk for experiencing psychosocial disorders